Pathologic complete response and survival after neoadjuvant chemotherapy in cT1-T2/N0 HER2+ breast cancer - Selena J. An; Emilie D. Duchesneau; Paula D. Strassle; Katherine Reeder-Hayes; Kristalyn K. Gallagher; David W. Ollila; Stephanie M. Downs-Canner; Philip M. Spanheimer (npj Breast Cancer, 2022)
Abstract Women with small HER2+ breast cancers may have excellent prognosis with adjuvant single-agent chemotherapy and HER2-targeted therapy. The role of de-escalated therapy in the neoadjuvant setting, however, remains uncertain. We conducted a cohort study of adult women with T1-2/cN0 HER2+ breast cancer diagnosed 2013–2016 in the National Cancer Database treated with neoadjuvant chemotherapy (NAC) and HER2-targeted therapy. Factors associated with pathologic complete response (pCR) and overall survival were examined. In total, 6994 patients were included, 32% cT1 and 68% cT2. Multi-agent NAC was given to 90% of women while single-agent NAC was given to 10% of women. pCR was achieved in 46% of cT2 patients and 43% of cT1, and in 46% of patients treated with multi-agent versus 38% single agent. Patients receiving multi-agent chemotherapy were younger, had fewer comorbidities, and had higher cT stage and grade. In all patients, pCR was associated with improved survival (p < 0.01). Multi-agent chemotherapy (OR 1.3, p = 0.003), hormone receptor negative (OR 2.6, p < 0.001), higher grade (OR 2.2, p < 0.001), younger age (OR 1.4, p = 0.011), and later year of diagnosis (OR 1.3, p = 0.005) were associated with achieving pCR. Multi-agent chemotherapy was associated with higher likelihood of pCR, but this effect was modest compared to other factors. Single-agent NAC with HER2-directed therapy in selected patients may provide excellent outcome with reduced toxicity, while allowing escalated therapy in the adjuvant setting for patients with residual disease. Prospective studies are needed to determine effects of de-escalation in the neoadjuvant setting on survival and optimal selection strategies.